Production and characterization of surfactin-like biosurfactant produced by novel strain Bacillus nealsonii S2MT and it's potential for oil contaminated soil remediation - Phulpoto, Irfan Ali; Yu, Zhisheng; Hu, Bowen; Wang, Yanfen; Ndayisenga, Fabrice; Li, Jinmei; Liang, Hongxia; Qazi, Muneer Ahmed (Microbial cell factories, 2020)
Biosurfactants, being highly biodegradable, ecofriendly and multifunctional compounds have wide applications in various industrial sectors including environmental bioremediation. Surfactin, a member of lipopeptide family, which is considered as one of the most powerful biosurfactants due to its excellent emulsifying activities as well as environmental and therapeutic applications. Therefore, the aim of this study was to investigate the newly isolated bacterial strain S2MT for production of surfactin-like biosurfactants and their potential applications for oil-contaminated soil remediation. In this study, the strain S2MT was isolated from lake sediment and was identified as Bacillus nealsonii based on transmitted electron microscopy (TEM) and 16S rRNA ribo-typing. The strain S2MT produced biosurfactant that reduced the surface tension (34.15 ± 0.6 mN/m) and displayed excellent emulsifying potential for kerosene (55 ± 0.3%). Additionally, the maximum biosurfactant product yield of 1300 mg/L was achieved when the composition of the culture medium was optimized through response surface methodology (RSM). Results showed that 2% glycerol and 0.1% NH NO were the best carbon/nitrogen substrates for biosurfactant production. The parameters such as temperature (30 °C), pH (8), agitation (100 rpm), NH NO (0.1%) and NaCl (0.5%) displayed most significant contribution towards surface tension reduction that resulted in enhanced biosurfactant yield. Moreover, the extracted biosurfactants were found to be highly stable at environmental factors such as salinity, pH and temperature variations. The biosurfactants were characterized as cyclic lipopeptides relating to surfactin-like isoforms (C -C ) using thin-layer chromatography (TLC), Ultra high performance liquid chromatography and mass spectrometry (UHPLC-MS). The crude biosurfactant product displayed up to 43.6 ± 0.08% and 46.7 ± 0.01% remediation of heavy engine-oil contaminated soil at 10 and 40 mg/L concentrations, respectively. Present study expands the paradigm of surfactin-like biosurfactants produced by novel isolate Bacillus nealsonii S2MT for achieving efficient and environmentally acceptable soil remediation as compared to synthetic surfactants.